Serum anti-GM2 and anti-GalNAcGD1a IgG antibodies are biomarkers for acute canine polyradiculoneuritis - Mateo Pampliega, Isidro; Halstead, S.K.; Gourlay, D.S; Penderis, J.; Bianchi, E.; Dondi, M.; Wessmann, A.; Musteata, M.; Le Chevoir, M.; Martinez-Anton, L.; Bhatti, S.F.M.; Volk, H. (My University, 2021)
Objectives: A previous single-country pilot study indicated serum anti-GM2 and anti-GA1 anti-glycolipid antibodies as potential biomarkers for acute canine polyradiculoneuritis. This study aims to validate these findings in a large geographically heterogenous cohort. Materials and Methods: Sera from 175 dogs clinically diagnosed with acute canine polyradiculoneuritis, 112 dogs with other peripheral nerve, cranial nerve or neuromuscular disorders and 226 neurologically normal dogs were screened for anti-glycolipid antibodies against 11 common glycolipid targets to determine the immunoglobulin G anti-glycolipid antibodies with the highest combined sensitivity and specificity for acute canine polyradiculoneuritis. Results: Anti-GM2 anti-glycolipid antibodies reached the highest combined sensitivity and specificity (sensitivity: 65.1%, 95% confidence interval 57.6 to 72.2%; specificity: 90.2%, 95% confidence interval 83.1 to 95.0%), followed by anti-GalNAc-GD1a anti-glycolipid antibodies (sensitivity: 61.7%, 95% confidence interval 54.1 to 68.9%; specificity: 89.3%, 95% confidence interval 82.0 to 94.3%) and these anti-glycolipid antibodies were frequently present concomitantly. Anti-GA1 anti-glycolipid antibodies were detected in both acute canine polyradiculoneuritis and control animals. Both for anti-GM2 and anti-GalNAc-GD1a anti-glycolipid antibodies, sex was found a significantly associated factor with a female to male odds ratio of 2.55 (P=0.0096) and 3.00 (P=0.0198), respectively. Anti-GalNAc-GD1a anti-glycolipid antibodies were more commonly observed in dogs unable to walk (odds ratio 4.56; P=0.0076). Clinical Significance: Anti-GM2 and anti-GalNAc-GD1a immunoglobulin G anti-glycolipid antibodies represent serum biomarkers for acute canine polyradiculoneuritis. © 2021 The Authors. Journal of Small Animal Practice published by John Wiley & Sons Ltd on behalf of British Small Animal Veterinary Association